2017
DOI: 10.1002/jssc.201700761
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative analysis of multiple compounds in raw and prepared Semen Cassiae coupled with multiple statistical strategies

Abstract: In China, Semen Cassiae is used clinically to improve eyesight, relieve constipation, and to treat headache and dizziness. Prepared Semen Cassiae is obtained by stir-frying raw Semen Cassiae until it turned dark brown, micro dilatancy, and overflow aroma. After processing, the therapeutic effects change-the purgation effect is alleviated and the hepatoprotective effect is enhanced. To explore the changes in chemical compositions of Semen Cassiae after processing and clarify the material basis of the changed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…8 Upon processing the medicinal agents, changes in their chemical compounds in the form of increase or reduction of content, and the formation or disappearance of specic compounds were observed. 9,10 Notably, the preceding reports highlight an increase in ARG content and an overall decrease in ARC aer the stir-frying process. 11 Nevertheless, the functioning mechanism of the activity changes remained obscure even aer the process of stir-frying in vivo.…”
Section: Introductionmentioning
confidence: 93%
“…8 Upon processing the medicinal agents, changes in their chemical compounds in the form of increase or reduction of content, and the formation or disappearance of specic compounds were observed. 9,10 Notably, the preceding reports highlight an increase in ARG content and an overall decrease in ARC aer the stir-frying process. 11 Nevertheless, the functioning mechanism of the activity changes remained obscure even aer the process of stir-frying in vivo.…”
Section: Introductionmentioning
confidence: 93%
“…Several analytical techniques have been used for qualitative and quantitative analysis of active components in RSC and PSC , and more than 70 components are identified, including anthraquinones, naphthopyrones, volatile oils, and sterols. Among these, anthraquinones and naphthopyrones are the primary active components exhibiting multiple pharmacological activities , and the content of them in RSC and PSC have significant difference . In our previous investigation, some anthraquinones and naphthopyrones, aurantio‐obtusin, obtusin, chrysoobtusin, obtusifolin, emodin, chrysophanol, aloe‐emodin, rhein, and physcion, may be the main active components of Semen Cassiae, and their chemical structure of the nine components are depicted in Figure .…”
Section: Introductionmentioning
confidence: 94%
“…Seeds of Cassia obtusifolia , called juemingzi in Chinese have been widely used in drinks and traditional Chinese medicine for heat clearing, eyesight improvement, dizziness treatment, and constipation relief [20]. Phytochemical studies indicated that anthraquinones and naphthopyrones are the main chemical compounds in C. obtusifolia , while two anthraquinone aglycones, chrysophanol and aurantio‐obtusin, have been considered as the official quality markers [20,21]. Modern pharmacological studies revealed the antitumor, antioxidant, antimicrobial, antidiarrhoeal, and hypolipidemic activities of C. obtusifolia [22].…”
Section: Introductionmentioning
confidence: 99%
“…Modern pharmacological studies revealed the antitumor, antioxidant, antimicrobial, antidiarrhoeal, and hypolipidemic activities of C. obtusifolia [22]. To date, more attentions about C. obtusifolia have been paid to the qualitative/quantitative analysis of chemical compounds by HPLC–MS [21], isolation of major chemical compounds by different chromatography technologies [22,23], and biological investigation of crude extract, fraction, or purified compounds [24]. Therefore, a novel method to rapid and systematic investigation of bioactive compounds in C. obtusifolia is highly required.…”
Section: Introductionmentioning
confidence: 99%